Case of Recurrent Episode of Schizoprenia Paranoid in Pregnant Woman - Setiobudi, Karen Delicia; Soetjipto, Soetjipto; Damba Bestari; Era Catur Prasetya (Faculty of Medicine, Universitas Airlangga, 2023)
AbstractIntroductions: Pregnancy is a stressor to women, in terms of biological as well as psychological. For individuals who previously received medication for schizophrenia in the past, it can be a triggering factor for the relapse of the illness. Here we describe a case of a pregnant woman who experiences a relapse in pregnancy. Case: The patient was a 40-year-old pregnant woman, brought to the emergency room after attacking her father by stabbing her father's head with a knife. She was suspicious of her dad's gaze at her. She was hostile towards healthcare workers when being examined. For her pregnancy, consultation with the Obstetric and Gynaecology department had been done to ensure that she and her baby were taken care of while being treated in the psychiatry ward. Discussions: The patient was diagnosed as having paranoid schizophrenia recurrent episodes. There was no complication found in her pregnancy, and she was scheduled for Sectio Caesarean as she was not mentally fit to do vaginal delivery. The psychiatric approach to the patient was atypical antipsychotic along with supportive psychotherapy. Psychoeducation and family therapy were also done to ensure that the patient's family understand the illness and the importance of compliance with the medication. Conclusions: Pregnancy is one of the factors that lead to the relapse of schizophrenia in patients with a history of mental illness. Holistic treatment is needed to treat the patient to prevent the relapse of the illness.